Heteroleptic [Bis(oxazoline)](dipyrrinato)zinc(II) Complexes: Bright and Circularly Polarized Luminescence from an Originally Achiral Dipyrrinato Ligand. Issue 4 (10th December 2015) - Kögel, Julius F.; Kusaka, Shinpei; Sakamoto, Ryota; Iwashima, Toshiki; Tsuchiya, Mizuho; Toyoda, Ryojun; Matsuoka, Ryota; Tsukamoto, Takamasa; Yuasa, Junpei; Kitagawa, Yasutaka; Kawai, Tsuyoshi; Nishihara, Hiroshi
Abstract: Heteroleptic zinc(II) complexes synthesized using achiral dipyrrinato and chiral bis(oxazoline) ligands show bright fluorescence with quantum efficiencies of up to 0.70. The fluorescence originates from the 1 π–π * photoexcited state localized exclusively on the dipyrrinato ligand. Furthermore, the luminescence is circularly polarized despite the achirality of the dipyrrinato ligand. Single‐crystal X‐ray structure analysis discloses that the chiral bis(oxazoline) ligand undergoes intramolecular π–π stacking with the dipyrrinato ligand, inducing axial chirality in the dipyrrinato moiety. Abstract : The odd couple : Heteroleptic zinc(II) complexes synthesized using achiral dipyrrinato (shown in magenta) and chiral bis(oxazoline) ligands (turquoise) show bright fluorescence from the dipyrrinato moiety with quantum efficiencies of up to 0.70. The luminescence is circularly polarized, which results from axial chirality induction to the dipyrrinato ligand by the bis(oxazoline) ligand.